Exploring rapport management among culturally diverse students during group work face-to-face interactions: a qualitative study - Ong, Sue Lyn (Penerbit Universiti Kebangsaan Malaysia, 2023)
Group work skills are commonly viewed as an important generic outcome of university for all students. Often, students working in groups for course assignments engage in potentially face-threatening interactions during discussions. The complication is compounded when students represent culturally diverse backgrounds in such intercultural communication.This study describes the rapport management that takes place during face-to-face group work interactions and examines the complex negotiation of social categories during intercultural group work interactions. This ethnographically informed qualitative study involved participants who were first-year undergraduates taking a course in English for Business. Their group discussions were observed in-situ, interactions were audio-taped and then transcribed for analysis. The study investigates the social intercultural interactions using Rapport Management as a framework to analyse intercultural interactions based on the concepts of face, sociality rights, and interactional goals. The findings confirm that rapport orientation is a key influence in strategy choice driven by the constructed social categories of the participants. Individual social categories are co-constructed and negotiated during the interaction processes. In face-threatening situations, the participants would orient to rapport-neglect and rapport-challenge during an interaction, but they would finally orientate to rapport-maintenance to achieve the successful interactional goals of group work. The study contributes towards the body of knowledge and understanding on rapport management and social categories in group work interactions in the context of a Malaysian university. The findings suggest that education practitioners need to be more interculturally competent in understanding the dynamics of intercultural communication among students during their participation in group work.